2015
DOI: 10.1103/physrevb.91.165123
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electron correlations at theSrxCa1xVO3surface

Abstract: We report hard x-ray photoemission spectroscopy measurements of the electronic structure of the prototypical correlated oxide SrxCa1−xVO3. By comparing spectra recorded at different excitation energies, we show that 2.2 keV photoelectrons contain a substantial surface component, whereas 4.2 keV photoelectrons originate essentially from the bulk of the sample. Bulk sensitive measurements of the O 2p valence band are found to be in good agreement with ab initio calculations of the electronic structure with some … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…All this indicates that correlation effects are strongly enhanced at the surface relative to the inner layers, in good agreement with experimental observations for CaVO 3 and the closely related material SrVO 3 [33,34,51,52] and previous DFT+DMFT calculations for SrVO 3 [35,53]. In particular, close to U mit but still in the metallic phase, the surface seems to form a "dead layer", with nearly vanishing quasiparticle weight, as discussed in Ref.…”
Section: Effect Of Dimensional Confinementsupporting
confidence: 91%
“…All this indicates that correlation effects are strongly enhanced at the surface relative to the inner layers, in good agreement with experimental observations for CaVO 3 and the closely related material SrVO 3 [33,34,51,52] and previous DFT+DMFT calculations for SrVO 3 [35,53]. In particular, close to U mit but still in the metallic phase, the surface seems to form a "dead layer", with nearly vanishing quasiparticle weight, as discussed in Ref.…”
Section: Effect Of Dimensional Confinementsupporting
confidence: 91%
“…The quasi two-dimensional (2D) rare-earth tritellurides RTe3 (R = La-Nd, Sm, Gd-Tm) are prime examples of CDW ordered ground states. Angle-resolved photoemission spectroscopy (ARPES) measurements [16] [17] of several rare-earth tritelluride compounds lead to the assumption of a nesting driven CDW order and, hence, RTe3 are often regarded as canonical Peierls-like CDW systems. On the other hand, theoretical investigations of RTe3 [18] revealed a nesting feature, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It has been pointed out by Sarma and co-workers [10,11] that the incoherent part for SrVO 3 and CaVO 3 has a lot of contributions from surface states through photoemission studies using different photon energies. In fact, a recent hard x-ray photoemission study revealed enhanced coherent spectral weight due to the bulk sensitivity [12]. Therefore, one should be careful when the spectral weight transfer and the effect of electron correlation are analyzed quantitatively.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a recent hard x-ray photoemission study revealed enhanced coherent spectral weight due to the bulk sensitivity [12]. Therefore, one should be careful when the spectral weight transfer and the effect of electron correlation are analyzed quantitatively.…”
mentioning
confidence: 99%